Auricular ossification: A newly recognized feature of osteoprotegerin‐deficiency juvenile Paget disease. Issue 4 (14th January 2016) - Gottesman, Gary S.; Madson, Katherine L.; McAlister, William H.; Nenninger, Angela; Wenkert, Deborah; Mumm, Steven; Whyte, Michael P.
Abstract : We report auricular ossification (AO) affecting the elastic cartilage of the ear as a newly recognized feature of osteoprotegerin (OPG)‐deficiency juvenile Paget disease (JPD). AO and auricular calcification refer interchangeably to rigid pinnae, sparing the ear lobe, from various etiologies. JPD is a rare Mendelian disorder characterized by elevated serum alkaline phosphatase activity accompanied by skeletal pain and deformity from rapid bone turnover. Autosomal recessive transmission of loss‐of‐function mutations within TNFRSF11B encoding OPG accounts for most JPD (JPD1). JPD2 results from heterozygous constitutive activation of TNFRSF11A encoding RANK. Other causes of JPD remain unknown. In 2007, we reported a 60‐year‐old man with JPD1 who described hardening of his external ears at age 45 years, after 4 years of treatment with bisphosphonates (BPs). Subsequently, we noted rigid pinnae in a 17‐year‐old boy and 14‐year‐old girl, yet pliable pinnae in a 12‐year‐old boy, each with JPD1 and several years of BP treatment. Cranial imaging indicated cortical bone within the pinnae of both teenagers. Radiologic studies of our three JPD patients without mutations in TNFRSF11B showed normal auricles. Review of the JPD literature revealed possible AO in several reports. Two of our JPD1 patients had experienced difficult tracheal intubation, raising concern for mineralization of laryngeal elastic cartilage. Thus, AO is a newly recognized feature of JPD1, possibly exacerbated by BP treatment. Elastic cartilage at other sites in JPD1 might also ossify, and warrants investigation. © 2016 Wiley Periodicals, Inc.